A Staphylococcus aureus Coinfection on a COVID-19 Pneumonia in a Breast Cancer Patient - Spoto, Silvia (Int J Gen Med, 2020)
INTRODUCTION: Coronavirus disease 19 (COVID-19), due to severe acute respiratory syndrome-coronavirus 2 (SARS-CoV2), comprises a broad spectrum of clinical presentation ranging from flu-like syndrome to organ failure. The risk of coinfections is high and responsible for a worse prognosis, mainly in the case of bacterial involvement and in the presence of particular comorbidity. We present the clinical, laboratory, radiologic characteristic along with therapeutic management of a patient with COVID-19 and Staphylococcus aureus coinfection. CASE PRESENTATION: A 55-year-old Caucasian woman was admitted to our hospital due to a two-day history of fever and acute dyspnea with severe respiratory failure worsened after the administration of atezolizumab and nab-paclitaxel. Her medical history comprehended a triple negative, BRCA1-related, PD-L1 positive right breast cancer with multiple bone metastasis, causing bone marrow infiltration-related severe pancytopenia. Her physical examination revealed scattered wheezes, rales, and bilateral dry crackles in the middle and lower lung fields and lower limb paresis. The body mass index was 30 kg/m(2) and arterial blood gas evaluation revealed a stage III acute respiratory distress syndrome. Microbiological specimens revealed a Staphylococcus aureus positivity from endotracheal aspirate. The chest computed tomography (CT) scan showed the presence of large areas of parenchymal consolidation and aerial bronchogram, bilateral “ground glass” areas reaching the highest extension on the upper and middle zones. The high clinical and radiological suspicion of COVID-19 along with the negative result of nasopharyngeal specimen make necessary an endotracheal aspirate resulting positive for SARS-CoV2. Patient started an antimicrobial treatment and lopinavir-ritonavir plus hydroxychloroquine but, unfortunately, died five days after hospital admission. CONCLUSION: The high risk of mortality of our patient was due to viral-bacterial coinfection, advanced cancer status with active immunotherapy. This case highlights the need for a prompt clinical, laboratory, and radiological evaluation to allow a correct diagnosis and start a specific therapy.